2020
DOI: 10.1021/acscatal.0c02567
|View full text |Cite
|
Sign up to set email alerts
|

Improved Activity and SO2 Resistance by Sm-Modulated Redox of MnCeSmTiOx Mesoporous Amorphous Oxides for Low-Temperature NH3-SCR of NO

Abstract: The selective catalytic reduction (SCR) technique that converts NO x from the outlet of industrial boilers at low temperature (<200 °C) requires catalysts that possess both the oxidization property of NO x and the adsorption ability to NH 3 . However, owing to unsuitable redox capacity, most NH 3 -SCR catalysts such as MnO 2 /TiO 2 and MnO 2 −CeO 2 /TiO 2 suffer from poor activity and N 2 selectivity and SO 2 poisoning. Benefiting from constructing mesoporous MnCeSmTiO x amorphous mixed oxides by the coprecipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
67
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 223 publications
(74 citation statements)
references
References 59 publications
6
67
0
1
Order By: Relevance
“…5a and b) and all fitted with three peaks: Mn 4+ (∼643.5 and ∼655.2 eV), Mn 3+ (∼641.8 and ∼653.5 eV), and Mn 2+ (∼640.5 and 652.2 eV). 28,41,42 Even the previous XRD results did not show the presence of the Mn 4+ species, and XPS could detect Mn 4+ on the catalyst surface. The (Mn 3+ + Mn 4+ )/Mn (via peak area) ratios of these samples showed an ascending trend and then a descending trend with the increasing amount of introduced Fe element.…”
Section: Characterizationmentioning
confidence: 68%
“…5a and b) and all fitted with three peaks: Mn 4+ (∼643.5 and ∼655.2 eV), Mn 3+ (∼641.8 and ∼653.5 eV), and Mn 2+ (∼640.5 and 652.2 eV). 28,41,42 Even the previous XRD results did not show the presence of the Mn 4+ species, and XPS could detect Mn 4+ on the catalyst surface. The (Mn 3+ + Mn 4+ )/Mn (via peak area) ratios of these samples showed an ascending trend and then a descending trend with the increasing amount of introduced Fe element.…”
Section: Characterizationmentioning
confidence: 68%
“…S4). Wang et al [54] also demonstrated the superiority of the Sm modified catalyst. Compared with catalysts without Sm, mesoporous MnCeSmTiOx mixed oxides maintained higher catalytic performance after H2O and SO2 were added by suppressing the oxidation of SO2 by Mn 4+ and Ce 4+ .…”
Section: Manganese-based Catalystsmentioning
confidence: 95%
“…Specifically, the bonds marked u' and v' represent the 3d 10 4f 1 states of Ce 3 + initial electronic, and the bands marked u, u'', u''', v, v'' and v''' represent the 3d 10 4f 0 states of the Ce 4 + . [51,52] According to reports in the literature, [53] the high content of Ce 3 + contributes to formed more oxygen vacancies and promoted adsorption of HN 3 . For the sulfur-treated catalyst, the content of Ce 3 + had slightly decreased, this phenomenon demonstrated that there was charge transfer between Ce 3 + and Ce 4 + in the SCR process, the conversion between Ce 4 + and Ce 3 + also related to the storage and release of oxygen from CeO 2 .…”
Section: Surface State Analysismentioning
confidence: 97%